2022
DOI: 10.1111/jonm.13697
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol, perceived stress and coping strategies: A comparative study of working and nonworking women

Abstract: Aims: This study investigated stress levels and coping strategies among working and nonworking women in the United Arab Emirates.Background: Stress levels in working and nonworking women have previously been studied, but few studies used cortisol to measure stress or examined how coping strategies affect stress levels.Methods: We employed a cross-sectional design with a convenience sample of women aged 20-65 years. Information on women's sociodemographic characteristics, perceived stress (using the Perceived S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous research findings stated that anxiety, stress and depression in working and non-working women were influenced differently by social support and marital status 10 . Women who do not work have higher levels of stress than women who work 11 . Previous researchers reported that working and Pharmacognosy Journal, Vol 16, Issue 2, Mar-Apr, 2024 married women have better reproductive health status than working women who are not married or divorced 12. Anxiety arises from facing a threatening situation 13 .…”
Section: Introductionmentioning
confidence: 91%
“…Previous research findings stated that anxiety, stress and depression in working and non-working women were influenced differently by social support and marital status 10 . Women who do not work have higher levels of stress than women who work 11 . Previous researchers reported that working and Pharmacognosy Journal, Vol 16, Issue 2, Mar-Apr, 2024 married women have better reproductive health status than working women who are not married or divorced 12. Anxiety arises from facing a threatening situation 13 .…”
Section: Introductionmentioning
confidence: 91%
“…At the same time, only a limited number of women in the UAE engage in scientific research mainly due to lack of confidence in women's capacities to conduct scientific research while balancing other familial duties (Bani‐Issa et al, 2022). This is mainly due to social pressure, stereotyping and bias in recruitment and hiring in some sectors.…”
Section: Year Number Of Applicants Number Of Participating Universiti...mentioning
confidence: 99%